Ecological adaptability assessment for adaptive management of island social–ecological systems: a potential–constraint framework applied to Dongtou District, China - Yunyun Xiang; Cifang Wu (Frontiers in Marine Science, 2026)
Introduction Artificial Island social–ecological systems face escalating, compound pressures from global environmental change and intensive human activities, while conventional post-hoc restoration approaches are often insufficient to ensure long-term sustainability. We propose an ecological adaptability assessment framework to support proactive, policy-responsive adaptive management. Methods We develop a potential–constraint framework that couples scenario-based spatial modeling with explicit policy feedback. Using Dongtou District (Zhejiang Province, China) as a representative case, we quantify trade-offs between ecological resilience and development potential under alternative policy trajectories. A multidimensional indicator system—covering habitat structure, ecosystem function, socio-economic conditions, marine utilization, and governance responses—is integrated into a gridded modeling platform to identify adaptive management pathways toward 2030. Results Ecological adaptability exhibits pronounced spatial heterogeneity: high-adaptability zones align with ecological reserves, whereas low-adaptability zones cluster on densely inhabited and industrialized islands. Scenario simulations indicate that policy orientation decisively reshapes adaptability patterns. Among the evaluated pathways, the eco–economic coordination scenario delivers the most balanced configuration, improving spatial connectivity and mitigating landscape fragmentation. Discussion The proposed framework provides a transferable, policy-linked approach that bridges ecological evaluation with spatial governance, offering actionable evidence to design and prioritize island adaptive management strategies.